(untitled) (Journal of Universal Science Research, 2023)
In this article, the reforms implemented in the spheres of production and services are an important factor in ensuring employment of the population, increasing incomes and living standards of the population. At present, the organization of seminars and training courses on information technologies and advanced trading technologies for retailers will help to solve this issue in our country.